Femtosecond laser-induced interconnection of multi-walled carbon nanotubes. (18th August 2019) - Mei, Huanhuan; Cheng, Yang; Wang, Haojie; Duan, Wenqiang; Yang, Jun
Abstract: As conducting wires' sizes are scaled down, the carbon nanotubes (CNTs) as conducting wires instead of copper wires for integrated circuits have become significant, which the quantum effect become evident owing to their one-dimensional structure, excellent electrical, thermal and mechanical properties. The interconnection technology of carbon nanotubes is an indispensable part of structural manufacturing, functional device preparation and its assembly. Based on the principle of multiphoton non-linear absorption of femtosecond lasers, laser induced multi-walled carbon nanotubes (MWCNTs) connection experiments were carried out using femtosecond laser at wavelength of 800nm. With the change of laser energy, the morphologies of MWCNTs wound change accordingly, and it can interconnect with 80mW at a scanning rate of 25 μm/s. When the laser energy is higher than 100mW, MWCNTs can be modified and some unknown, circular nanosphere can be produced.